History and climate science: a collaborative relationship for the twenty-first century - Williamson, Fiona (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2015)
History as a subject for higher education (and beyond) has often been criticized for failing to be relevant to the demands of the twenty-first century. This paper argues that not only is learning from our past a valuable exercise in any time period, but that historical research can provide modern sciences with the much needed data and contextual analysis crucial to understanding many of the problems facing our world today. Based on research from historic archives in the UK and Malaysia, this paper explains how historians are recovering historic data invaluable to modern climate science, and demonstrates just how this data is being used.